Cyclostationarity-based filtering for narrowband interference suppression in direct-sequence spread-spectrum systems. - Gelli, G.
This paper addresses the problem of narrowband interference suppression in direct-sequence spread-spectrum (DS/SS) techniques, which have been adopted to implement code division multiple access (CDMA) systems for wireless mobile communications. The theory of cyclic Wiener filtering, based on the cyclostationarity assumption for the signals involved in the reception problem, is applied to design single-channel adaptive frequency-shift filters which exploit both temporal and spectral correlation properties, i.e., the correlation between time- and frequency-shifted versions of the received signal. The numerical results show that receiving structures based on the proposed cyclostationarity-based interference suppression schemes largely outperform receivers that utilize conventional linear time-invariant suppressors, when they operate in highly contaminated interference environments
Keywords: CDMA systems; DS/SS.; Code division multiple access; Cyclic Wiener filtering; Cyclostationarity-based filtering; Direct-sequence spread-spectrum systems; Frequency-shifted version; Highly contaminated interference environments; Narrowband interference suppression; Received signal; Receiving structures; Single-channel adaptive frequency-shift filters; Spectral correlation properties; Temporal correlation properties; Time-shifted version; Wireless mobile communications